A non-classical van der Waals loop: Collective variables method - Romanik, R.V.; Kozlovskii, M.P. (Condensed Matter Physics, 2013)
The equation of state is investigated for an Ising-like model in the framework of collective variables method. The peculiar feature of the theory is that a non-classical van der Waals loop is obtained. The results are compared with ones of a trigonometric parametric model, in terms of normalized magnetization, M, and field, H. Проводиться дослiдження рiвняння стану iзинґоподiбної моделi в рамках методу колективних змiнних.
У використаному пiдходi одержується некласична форма петлi ван дер Ваальса. Проводиться порiвняння, в термiнах перенормованих змiнних намагнiченостi i поля, отриманих результатiв для петлi ван дер Ваальса з результатами тригонометричної параметричної моделi представлення критичної поведiнки.